Sui legami categoriali della teoria della forma con l’antropologia filosofica classica del XX secolo - Czerniak, Stanisław (Filosofia, 2017)
The present paper intends to discuss the relationship between the XXth- century classic philosophical anthropology – the main representatives of which are Max Scheler and Helmut Plessner – and the theory of form. This relationship is discussed first of all from a historical viewpoint – as a source of intellectual inspiration in the case of Scheler’s philosophical anthropology; secondly, from a structural viewpoint, and with regard to Plessner’s position, with specific reference to its manifold theoretical and philosophical points in common with the “human models” of classic philosophical anthropology.